The pro- and anti-inflammatory cytokine response to exercise in adolescent swimmers - Wilson, L. D.; Zaldivar, F. P.; Schwindt, C. D.; Cooper, D. M. (Pediatric Asthma, Allergy & Immunology, 2009)
Whether or not individuals with allergy and asthma experience different patterns of change in the balance of both pro- and anti-inflammatory mediators with acute exercise is not known. We hypothesized that adolescent swimmers with a clinical diagnosis of respiratory allergy would have an exaggerated proinflammatory response to laboratory exercise relative to a no-allergy comparison group.